2009
DOI: 10.5194/hess-13-1427-2009
|View full text |Cite
|
Sign up to set email alerts
|

Future directions for hydropedology: quantifying impacts of global change on land use

Abstract: Abstract. Hydropedology is well positioned to address contemporary issues resulting from climate change. We propose a six-step process by which digital, field-scale maps will be produced to show where climate change impacts will be greatest for two land uses: a) home sites using septic systems, and b) wetlands. State and federal laws have defined critical water table levels that can be used to determine where septic systems will function well or fail, and where wetlands are likely to occur. Hydrologic models a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…地球关键带(Earth's Critical Zone)处于地表岩 石圈、 水圈、 土壤圈和生物圈的交互地带(图 1a), 地 球关键带土壤水文过程及其与环境因子之间的交 互关系是近年来国内外关注的新兴交叉研究方向 (Lin et al, 2005;Pachepsky et al, 2006;Vepraskas et al, 2009) (Bárdossy et al, 1998) (Mualem, 1976;van Genuchten, 1980…”
Section: 引言unclassified
“…地球关键带(Earth's Critical Zone)处于地表岩 石圈、 水圈、 土壤圈和生物圈的交互地带(图 1a), 地 球关键带土壤水文过程及其与环境因子之间的交 互关系是近年来国内外关注的新兴交叉研究方向 (Lin et al, 2005;Pachepsky et al, 2006;Vepraskas et al, 2009) (Bárdossy et al, 1998) (Mualem, 1976;van Genuchten, 1980…”
Section: 引言unclassified
“…Soil maps show the spatial distribution of mapping units and their soil horizons and they can be used to provide data for regional hydrological models, which are currently often only calibrated on limited base-flow data (e.g. A detailed analysis is beyond the scope of this text but Vepraskas et al (2006Vepraskas et al ( , 2009 have shown how pedological information on mottling patterns can be used to improve simulation of regional water regimes. But many problems remain because soil surveys provide no data on the internal variability of the mapping units (e.g.…”
Section: Characterizing Regional Flow Regimesmentioning
confidence: 99%
“…satellite data) with machine learning algorithms to explore the relationship between soil and hydrology 21 . Some works focused on how the soil and landscape attributes affect channels morphometry 22 26 , while others explored the behavior within the soil 27 – 30 . Thompson 1997 31 presented an early effort to quantitatively map HS through a soil color index using field sampling and terrain attributes derived from a digital elevation model.…”
Section: Introductionmentioning
confidence: 99%